ПОИСК МИКРОВОДОРОСЛЕЙ И МИКРООРГАНИЗМОВ, СИНТЕЗИРУЮЩИХ АРАХИДОНОВУЮ КИСЛОТУ И ЕЕ ПРОИЗВОДНЫЕ (Experimental biology, 2017)
It was a screening of the microalgae and microorganisms from soil and water of Kazakhstan on the ability of synthesize arahidon acid, using the test for sensitivity to acetilsalicil acid. Selected 4 strain for practical use to the development of biotechnology for arachidonic acid.
Keywords: microalgae; microorganisms; acetilsalicil acid; arahidon acid